Competence and Responsiveness in Mothers of Late Preterm Infants Versus Term Infants. Issue 3 (18th April 2013) - Baker, Brenda; McGrath, Jacqueline M.; Pickler, Rita; Jallo, Nancy; Cohen, Stephen
ABSTRACT Objective To compare maternal competence and responsiveness in mothers of late preterm infants (LPIs) with mothers of full‐term infants. Design A nonexperimental repeated‐measures design was used to compare maternal competence and responsiveness in two groups of postpartum mothers and the relationship of the theoretical antecedents to these outcomes. Setting Urban academic medical center. Participants Mothers of late preterm infants (34–36, 6/7‐weeks gestation) and mothers of term infants (≥37‐weeks gestation), including primiparas and multiparas. Data were collected after delivery during the postpartum hospital stay and again at 6‐weeks postpartum. Methods Descriptive and inferential analysis. Results A total of 70 mothers completed both data collection periods: 49 term mothers and 21 LPI mothers. There were no differences between the two groups related to their perception of competence or responsiveness at delivery or 6‐weeks postpartum. At 6‐weeks postpartum, none of the assessed factors in the model was significantly related to competence or responsiveness. Conclusions The results, which may have been limited by small sample size, demonstrated no difference in the perceptions of LPI and term mothers related to competence or responsiveness. Maternal stress and support were significantly related to other factors in the model of maternal competence and responsiveness.